Influencing factors of West Java higher education digital transformation - Sumartias, Suwandi; Koswara, Aang; Ahmad, Jamilah; Restianty, Ajani (Jurnal Kajian Komunikasi, 2024)
Background: Digital transformation, in this sense, means incorporating digital technology into many aspects of higher education, including learning, teaching, administration, and research. Purpose: This research aimed to generate a framework that is more knowledgeable than it was by utilizing digital technologies. In education, digital evolution attempts to establish an effective pleasant learning environment for everyone involved in a Smart Learning Environment. Methods: It employed an explanatory database analysis with multiple linear regression to examine the influencing factors of West Java’s higher education digital transformation. Results: The results indicated that digital transformation promotes more efficient work. However, there are also disadvantages, including reduced versatility, increased levels of student participation, and greater interaction among universities. It assures that the technology is dependable, functional, and satisfies stakeholders’ requirements. As they must adjust to the digital age and incorporate new methods and practices, higher education institutions play a significant role in the transition of the educational field. Conclusion: In education, digital transformation has demonstrated positive impacts, such as faster and more efficient work processes and increased access to information. Digital transformation also presents negative aspects, such as loss of flexibility, increased student involvement, and increased interactivity between universities. Implications: The application of technology information systems in higher education is significant for developing the education system. Transforming information technology systems in higher education is a strategic and enlightening vision for organizations, increasing efficiency, productivity, and accessibility.